`Erythropoietic' protoporphyria and cirrhosis in sisters. Issue 12 (December 1973) - Thompson, R. P. H.; Molland, E. A.; Nicholson, D. C.; Gray, C. H.
Abstract : The clinical and histopathological features of two sisters with erythropoietic protoporphyria and liver disease are described. They had unusually severe photosensitivity with blistering, and both died at the age of 31 from cirrhosis. The association of erythropoietic protoporphyria with several hepatic abnormalities is discussed.